Pengaruh Terapi Oketani terhadap Peningkatan Produksi ASI pada Ibu Primipara Pascapersalinan - Rina Milawati; Yuningsih; Sherlya (Journal Malnutrition, Public Health and Local Wisdom Nutrition, 2026)
The postpartum period is critical for establishing exclusive breastfeeding during the first six months of an infant’s life. However, primiparous postpartum mothers often experience inadequate milk production or impaired milk ejection due to flat or inverted nipples and ineffective milk flow. Oketani therapy is a non-pharmacological breast massage designed to improve breast tissue elasticity, stimulate the mammary glands, promote nipple protrusion, and facilitate milk ejection. This study aimed to determine the effect of Oketani therapy on breast milk production among primiparous postpartum mothers. This quantitative study employed a pre-experimental one-group pretest–posttest design. Data were collected using an observation sheet and the standard operating procedure for Oketani therapy. A total of 35 participants were selected through consecutive sampling. Breast milk production was compared before and after the intervention. The results showed a significant difference in breast milk production before and after Oketani therapy (p < 0.001), as indicated by an increased volume of breast milk after the intervention. Oketani therapy was effective in increasing breast milk production among primiparous postpartum mothers and may be recommended as a simple and practical independent nursing intervention. Keywords: breast milk production, Oketani therapy, postpartum mothers, primiparous mothers